Social Contagion and Information Technology Diffusion: The Adoption of Electronic Medical Records in U.S. Hospitals - Angst, Corey M.; Agarwal, Ritu; Sambamurthy, V.; Kelley, Ken (Management Science, 2010)
We use a social contagion lens to study the dynamic, temporal process of the diffusion of electronic medical records in the population of U.S. hospitals. Social contagion acknowledges the mutual influence among organizations within an institutional field and implicates information transmission through direct contact and observation as the mechanisms underlying influence transfer. We propose hypotheses predicting a hospital's likelihood of adopting electronic medical records as a function of its susceptibility to the influence of prior adopters, the infectiousness or potency of influence exerted by adopting hospitals, and its social and spatial proximity to prior adopters. Results obtained by fitting a heterogeneous diffusion model to data from a sample drawn from an annual survey, spanning 1975 to 2005, of almost 4,000 U.S. hospitals suggest that diffusion can be accelerated if specific attention is given to increasing social contagion effects. In particular, with respect to susceptibility to influence, greater hospital size and age are positively related to the likelihood of adoption for nonadopters, whereas younger hospitals are associated with greater infectiousness for adopters. A hospital's “celebrity” status also contributes to its infectiousness. We further find strong effects for social proximity and significant regional effects for spatial proximity and hospital size, suggesting that geographical covariates should be included in diffusion studies. Results also reinforce the importance of theorizing about and including interactions in examinations of social contagion.